Comparison of patient experiences of the glucagon and insulin pituitary provocation tests. (24th May 2012) - Katugampola, H; Spoudeas, HA
Abstract : Background: The debate surrounding which is the most suitable pituitary provocation test in children is controversial. There is a perception that the gold standard Insulin Tolerance Test (ITT) is "dangerous" and that the Glucagon Stimulation Test (GST) is "safer" and a more tolerable alternative, particularly in younger children. There have been no reports in the literature comparing patient experiences of these tests. Aim: To examine the tolerability of the GST compared to the ITT, by assessing the reported occurrence, duration and severity of adverse symptoms following administration of glucagon or insulin, and the impact of these symptoms on the patient's experience of their test. Methods: A prospective, qualitative cohort study was carried out over 3 months. The occurrence of any adverse symptoms and pre- and post-test levels of distress were ascertained by carrying out semi-structured interviews and administering structured questionnaires to children, age 8-17 years undergoing a GST or an ITT in a tertiary paediatric endocrinology centre. Results: 16 children constituted the study group (ITT n=8, GST n=8). 100% of children undergoing an ITT reported a fall in their distress score post-test, however 63% undergoing a GST reported a rise. Linear regression indicated the difference between group post-test scores was significant, with age and pre-test scores taken into account. On average the distress scores were +5.7 higher post-GST compared to post-ITT (p=0.001, 95% CI 2.8-8.6). The duration of occurrence of nonspecific (abdominal pain (p=0.007), hunger (p=0.001)) and neuroglycopenic (headache (p=0.007)) symptoms was significantly increased in the GST group compared to the ITT group. In contrast symptoms described by children undergoing an ITT were mainly autonomic and non-specific, and of greater severity but shorter duration. Conclusion: The significantly protracted duration of non-specific and neuroglycopenic symptoms reported by children undergoing a GST may have contributed to the rise in post-test distress scores, indicating decreased tolerability of the GST compared to the ITT. These preliminary findings should be interpreted cautiously in view of the small cohort, however this highlights the need for larger prospective studies in order to ascertain which is truly the safer, more efficacious and tolerable pituitary provocation test in children.